PROCESSING AND UTILIZATION OF TROPICAL ROOT CROPS I. PHYSICO-CHEMICAL CHARACTERIZATION OF COCOYAM STARCHES - Lauzon, Roberta D.; Kawabata, Akiko (Annals of Tropical Research, 1992)
Starch was produced from red and white cocoyams following the method developed by the Food Science Section of the Department of Agricultural Chemistry and Food Science (DAC-FS), VISCA, Baybay, Leyte. Purified starch samples were used in the analytical works. Granular size distribution and x-ray diffraction pattern determination were carried following the methods used by Kawabata et al. (1981) and Nakagawa (1973), respectively. Chemical properties were determined using the standard methods set by the Association of Official Analytical Chemist (AOAC, 1980). Starch granules of red and white cocoyams were spherical and semi-spherical in shape. Starch granules of red cocoyam were bigger than starch granules of white cocoyam. Starches from both cocoyams belonged to C type. Moisture content of red and white cocoyam starch was 11.49% and 11.99%, respectively. Inorganic matters content (P, K, Ca and Mg) were higher in red cocoyam than in white cocoyam starch.